2021
DOI: 10.1038/s41467-021-24716-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of non-stabilized alkyl radicals from thianthrenium salts for C–B and C–C bond formation

Abstract: Sulfonium salts bearing a positively charged sulfur atom with three organic substituents have intrigued chemists for more than a century for their unusual structures and high chemical reactivity. These compounds are known to undergo facile single-electron reduction to emerge as a valuable and alternative source of aryl radicals for organic synthesis. However, the generation of non-stabilized alkyl radicals from sulfonium salts has been a challenge for several decades. Here we report the treatment of S-(alkyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 90 publications
(89 reference statements)
0
62
0
2
Order By: Relevance
“…We recently developed an electrochemical strategy to engage oxidatively sensitive nucleophiles in net oxidative alkene difunctionalization reactions . Our approach draws inspiration from Yoshida’s pioneering cation pool work and contributes to a rapidly growing body of literature exploiting oxidized thianthrene derivatives as synthetic intermediates. Specifically, we leveraged electrochemistry to cleanly generate dicationic adducts between unactivated alkenes and thianthrene ( TT ), , a safe and inexpensive reagent. This strategy circumvents the need for oxidatively stable coupling partners in net oxidative alkene functionalization reactions; the oxidative alkene activation event is decoupled from nucleophilic substitution.…”
mentioning
confidence: 99%
“…We recently developed an electrochemical strategy to engage oxidatively sensitive nucleophiles in net oxidative alkene difunctionalization reactions . Our approach draws inspiration from Yoshida’s pioneering cation pool work and contributes to a rapidly growing body of literature exploiting oxidized thianthrene derivatives as synthetic intermediates. Specifically, we leveraged electrochemistry to cleanly generate dicationic adducts between unactivated alkenes and thianthrene ( TT ), , a safe and inexpensive reagent. This strategy circumvents the need for oxidatively stable coupling partners in net oxidative alkene functionalization reactions; the oxidative alkene activation event is decoupled from nucleophilic substitution.…”
mentioning
confidence: 99%
“…Alkyl sulfonium salt can be easily synthesised from alkyl halides, thiols and alcohols. [164][165][166][167][168] Upon receiving an electron, such a trivalent species undergoes R-S cleavage to release an Rc and a thioether. In 2018, MacMillan et al disclosed a Cu(II)/Ir(III) dual photocatalytic system to couple aryl bromides and tri-uoromethylsulfonium salt in the presence of a supersilanol (Scheme 41A).…”
Section: C-s Cleavagementioning
confidence: 99%
“…[22][23][24][25] Sulfonium salts are provided with photosensitivity, thereby generating aryl radicals. [26][27][28][29][30] In 2019, Ritter and coworkers extended the application of thiophene salts as precursors to the coupling of C-O, C-N and trifluoromethane with a wide range of functional groups (Scheme 1a), [31][32][33] laying the foundation for the late-stage highly selective functionalization of small molecules. Then Huang et al reported that by using visible light as a green energy source, redox-neutral borylation of aryl sulfonium salts via C-S activation could be achieved with moderate to good yields.…”
Section: Introductionmentioning
confidence: 99%